The Association Between Veteran Status and Obesity Differs Across Race/Ethnicity. Issue 2 (February 2022) - Cuevas, Adolfo G.; Cofie, Leslie E.; Nolte, Sarah
Purpose: This study aims to evaluate the interaction between veteran status and race/ethnicity on obesity status. Design: Cross-sectional survey Setting: The 2013–2017 National Health Interview Survey Sample: A total of 151, 765 adults (8.62% veterans and 91.38 nonveterans) with 69.30% identifying as White, 13.05% identifying as Hispanic, 12.57% identifying as Black, and 5.08% identifying as Asian Measures: Obesity status (measured using self-reported body mass index), race/ethnicity, survey year, age, marital status, educational attainment, federal poverty level, health insurance, type of insurance, self-reported health status, and whether participant had a usual care source. Analysis: Weighted logistic regression analysis Results: In a fully adjusted model, there was no evidence that veterans overall had higher odds of obesity compared to nonveterans (adjusted odd ratio (aOR): 1.05, 95% CI: .99, 1.11). White veterans had lower odds of obesity compared to White nonveterans (OR: .93, 95% CI: .87, .98). Hispanic veterans had higher odds of obesity compared to Hispanic nonveterans (aOR: 1.53, 95% CI: 1.23, 1.90). There was no evidence of an association between veteran status and obesity status for Black and Asian adults. Conclusions: Effectual prevention strategies are needed to decrease obesity risks among active and retired Hispanic veterans.